Developing nonarbitrary metrics for risk communication: norms for the Risk Matrix 2000 - Lehmann, Robert J. B. (Criminal justice and behavior, 2016)
Nominal risk categories for actuarial risk assessment information should be grounded in nonarbitrary, evidence-based criteria. The current study presents numeric indicators for interpreting one such tool, the Risk Matrix 2000, which is widely used to assess the recidivism risk of sexual offenders. Percentiles, risk ratios, and 5-year recidivism rates are presented based on an aggregated sample (N = 3,144) from four settings: England and Wales, Scotland, Germany, and Canada. The Risk Matrix 2000 Sex, Violence, and Combined scales showed moderate accuracy in assessing the risk of sexual, non-sexual violent, and violent recidivism, respectively. Although there were some differences across samples in the distributions of risk categories, relative increases in recidivism for ascending risk categories were remarkably consistent. Options for presenting percentiles, risk ratios, and absolute recidivism estimates in applied evaluations are offered, with discussion of the advantages, disadvantages, and limitations of these risk communication metrics.